THE MAIN ASPECTS OF EDUCATION BASED ON THE COMPETENCE APPROACH - Ashurova Moxigul Sodiq kizi (Journals Park Publishing, 2022)
This article reveals the main aspects of education based on the competency approach. In the research work, opinions on the characteristics of the formation of social competences are stated. Also, during the teaching process based on the competence approach, opinions were expressed about the formation of competencies to use the knowledge, skills and abilities acquired by students in their personal life, professional and social activities.
Keywords: Competence, student, external and internal factor